Tricuspid Valve Endocarditis due to Streptococcus bovis in a Patient with Ventricular Septal Defect: A Rare Manifestation—Case Report and Review of the Literature. (1st November 2017) - Pushpakumara, J.; Mudiyanse, G.; Jayawardana, A.; Siriwardana, J.; Shyamali, N. L. A.; Indrakumar, J.
Abstract : Streptococcus bovis endocarditis has 18%–62% association with colonic neoplasms with multivalvular involvement and affects mainly elderly males leading to severe cardiac dysfunction, septic embolization, and neurological complications. The aortic valve is the commonest valve to be affected followed by aortic and mitral valves together. However, involvement of tricuspid valve is extremely rare. There are no reported cases of Streptococcus bovis endocarditis affecting the tricuspid valve in the presence of ventricular septal defect with left to right shunt. We report the case of a 25-year-old female with ventricular septal defect who was diagnosed to have tricuspid valve endocarditis caused by Streptococcus bovis . Her detailed colonoscopy, upper gastrointestinal endoscopy, liver biochemistry, and ultrasound scan of the abdomen were normal. She made a very good recovery with six weeks of intravenous antibiotics. This is the first case of tricuspid valve endocarditis caused by Streptococcus bovis in association with ventricular septal defect without any colonic lesions.